Pengaruh Penggunaan Teknologi terhadap Keterlibatan siswa dalam Pembelajaran Pendidikan Agama Islam di Kota Sorong - Sella Nofriska Sudrimo; niswa zizah (MISOOL: Jurnal Pendidikan Dasar, 2019)
This study investigates the influence of digital technology use on students’ engagement in Islamic Religious Education (PAI) learning at SMA Averos Sorong. The rapid advancement of information technology has transformed the conventional model of PAI learning into a more flexible and interactive process. This research employs a quantitative correlational approach to determine the relationship between technology utilization and students’ behavioral, emotional, and cognitive engagement. Data were collected through a Likert-scale questionnaire distributed to 20 students of grade XII Math 1, whose responses were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and Spearman’s rho correlation test through Jamovi software. The findings reveal a positive correlation between the use of digital media and students’ engagement in PAI learning, with the strongest relationship found between emotional and cognitive dimensions. Students demonstrated greater enthusiasm, interest, and reflective thinking when teachers used visual and interactive digital tools such as videos and presentations. Although behavioral engagement showed a weaker correlation, technology use still contributed to a more active, enjoyable, and reflective learning atmosphere. In conclusion, the integration of digital technology in Islamic Religious Education at SMA Averos Sorong enhances students’ emotional and cognitive engagement, enriching their understanding of Islamic values through meaningful learning experiences. The study highlights the importance of teachers’ creativity in managing digital media to balance affective, cognitive, and behavioral aspects of student engagement.